The advantage of retrieval PEG tubes in patients with buried bumper syndrome - A case report - Gülbanu ERKAN; Mehmet ÇOBAN; Gökçe KAAN ATAÇ; Aysun ÇALIŞKAN; Bülent DEĞERTEKİN (Turkish Journal of Gastroenterology, 2019)
-